Identifying effective message-framing techniques in behaviour change communication for healthy diets: An experimental study of promoting biofortified maize adoption in Ethiopia - Jada, Kaleb Shiferaw; Berg, Marrit van den (Elsevier, 2022)
There is an increasing interest in using insights from behavioural economics and psychology to influence people's decisions. However, little is known as to how to leverage these insights to inform educational campaigns in the context of nutrition-sensitive agriculture. We help to fill this void by investigating the effect of framed messages (gain vs loss) in stimulating demand for nutritionally enhanced crops. We conducted a field experiment with 648 farmers and found the following key results. First, nutrition education stimulates demand for nutritionally enhanced crops among smallholder farmers. Without nutrition education, farmers are less likely to switch from producing conventional maize to nutritionally enhanced maize. Second, gain-framed messages are slightly more effective: they result in a higher willingness to pay for nutritionally enhanced maize than loss-framed messages. Third, motivational orientations and risk perceptions of individuals moderate the effect of the framed messages.